PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI HEAD OFFICE PT X JAKARTA TIMUR - Stella Bernadine (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
Training and Motivation are very important in improving employee’s performance. Training is deeply important for the company to train their employees in order to improve employee's competence and performance. Training provided to delivering employee’s knowledges, skills, and expertises to achieve their performance that expected by the company. Motivation is given relates to their work, motivation is to encourage them and creating their good performance for achieve the company’s objectives. This study aims to examine the effect of training and motivation on employee performance at Head Office of PT X in the East Jakarta. This study was conducted with the participation of 49 employees. Data collection method used is field research by using questionnaire instrument. Data analysis uses linear regression technique assited by SPSS. Hypothesis testing is done by F Test and t Test. This study conluded that both training and motivation have a positive effect on employee performance, partially and simultaneously. Keywords: training, motivation, performance